2021
DOI: 10.1186/s43055-021-00447-8
|View full text |Cite
|
Sign up to set email alerts
|

Does contrast-enhanced mammography have an impact on the detection of cancer in patients with risk of developing breast cancer?

Abstract: Background Contrast-enhanced mammography (CEM) has been discovered to be more sensitive and specific than two-dimensional full-field digital mammography (FFDM) in both screening and diagnostic settings. The aim of the study was to assess the additive role of CEM in the detection and characterization of breast lesions in women with increased risk of developing breast cancer. This prospective study included 283 female patients with increased risk of developing breast cancer (i.e., positive family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Our study results regarding the superiority of CEDM over FFDM in the diagnosis of multifocality, multicentricity, and bilaterality of breast cancer matches those reported by Moustafa et al (16) who concluded that CEDM had an offered value in the preoperative assessment of breast masses by enhancing the accuracy of lesions identification and multiplicity and Hashem et al (17) reported that CEDM enhances the BI-RADS evaluation of malignant cases and it is also useful in the detection of multifocal and multicentric lesions.…”
Section: Discussionsupporting
confidence: 89%
“…Our study results regarding the superiority of CEDM over FFDM in the diagnosis of multifocality, multicentricity, and bilaterality of breast cancer matches those reported by Moustafa et al (16) who concluded that CEDM had an offered value in the preoperative assessment of breast masses by enhancing the accuracy of lesions identification and multiplicity and Hashem et al (17) reported that CEDM enhances the BI-RADS evaluation of malignant cases and it is also useful in the detection of multifocal and multicentric lesions.…”
Section: Discussionsupporting
confidence: 89%